Ciência e confessionalidade: condição possível para a construção da Ciência da Religião - Siqueira, Antonio de Oliveira (Sacrilegens, 2017)
This article intends to discuss the possibility of constructing the Study of Religion with due exemption and distance, regardless of the creed of the one who produces the knowledge, taking into account mainly the discussion of the arguments about what is the epistemology of the Study of Religion, academic impurity in the vision of Antônio Flávio Pierucci, the comments and considerations of Marcelo Camurça, the process of building science and scientific distancing.